Severe Acute Radiation Dermatitis in a Patient with Argyria - P. Gorayski; M. B. Pinkham; J. B. Muir; A. P. Pullar (Case Reports in Oncological Medicine)
Argyria is a rare cutaneous condition due to dermal silver deposition leading to irreversible blue-grey discoloration. Acute radiation dermatitis (RD) is an expected toxicity in patients undergoing radiotherapy but it is unknown to what extent argyria affects the onset and severity of RD. We report a patient with argyria treated with concurrent chemoradiotherapy for Merkel cell carcinoma who experienced an unexpectedly brisk and severe RD during treatment. Possible mechanisms for this interaction are considered.